The use of the biologically activated grain is in technology of health products - Simahina, Galina; Bazhay-Zhezherun, Svitlana; Fedorenko (Mykoliv), Tetiana; Bereza-Kindzerska, Ludmyla; Antoniuk, Maria (My University, 2016)
The concept of scientific, methodical and technological support for learning logic is presented. The concept founds on the notions ofThe basic stages of technological process of production of semi-finished products or mixtures from grain, enriched by microelements, grounded. The mutual influence of microelements on content of amino acid in germinated grain of oat is determined. Ways of the processing enriched with mineral substances of grain raw materials it is offered. intensification of synthesis of vitamins is experimentally investigational in the process of germinating of wheat grain with the use of plant extracts that contain phytoncides. The technology of manufacturing health products is worked out on the basis of the biologically activated grain of wheat "ZerniatkoPikantne" (the kernel) with the extract of garlic or onion extract. Представлена концепція наукового, методичного та технологічного забезпечення логіки навчання. Концепція ґрунтується на уявленнях основних етапів технологічного процесу виробництва напівфабрикатів або сумішей з зерна, збагачених мікроелементами, обґрунтованих. Визначено взаємний вплив мікроелементів на вміст амінокислоти в пророслому зерні вівса. Запропоновано спосіб переробки, збагачений мінеральними речовинами зернової сировини. Інтенсифікація синтезу вітамінів експериментально досліджується в процесі проростання зерна пшениці з використанням рослинних екстрактів, що містять фітонциди. Технологія виробництва оздоровчих продуктів розроблена на основі біологічно активованого зерна пшениці «ZerniatkoPikantne» (ядро) з екстрактом часнику або цибульного екстракту.
Keywords: кафедра екології та екоменеджменту; biologicalactivation; mineralization; grain; oats; wheat; біологічна активація; мінералізація; зерно; овес; пшениця; биологическая активация; минерализация; пшениця; кафедра технології оздоровчих продуктів